Our Biometric Future : Facial Recognition Technology and the Culture of Surveillance. - Gates, Kelly A. (Critical cultural communication., 2011)
Since the 1960s, a significant effort has been underway to program computers to "see" the human face-to develop automated systems for identifying faces and distinguishing them from one another?commonly known as Facial Recognition Technology. While computer scientists are developing FRT in order to design more intelligent and interactive machines, businesses and states agencies view the technology as uniquely suited for "smart" surveillance-systems that automate the labor of monitoring in order to increase their efficacy and spread their reach. Tracking this technological pursuit, Our Biometric.